CRITERIA INDICATORS OF THE LEVEL OF FORMED CREATIVE SKILLS OF EDUCATIONAL CHARACTER IN STUDENTS (Pedagogy of Higher and Secondary Education, 2010)
The article describes the separate aspects of complex study of the formed level of creative abilities of graphic for students, characterizes territorial indexes.
Keywords: creation; creativeness; territor al indexes